E-Journal Usage Analysis in an Academic Library:A Case Study of a Publisher at a Technology Institute - Singh, Yogendra (Journal of Information and Knowledge, 2016)
This paper analyses the full text download statistics provided by one of the major publishers of Scientific and Technical (S&T) journals to a technology institute in India. Comparison of usage data for last five years (2007-2011) has been made. It identifies the top 10 most heavily used journals in all five years. Study reveals that the number of top titles which are responsible for 25% download is less than one percent in all the years. Numbers of titles which are responsible for next 25% download are in the range of 2-3%, for next 25% download 5-6% are in the range of 40-50% of the total number of journals. About 50% of the titles were never used. The percentage of titles shown above remained constant almost every year with very minor variations.